Desafios para a consolidação da regulação de serviços públicos no Estado do Ceará: o caso ARCE - Sabóia, Luís Alberto Aragão (2007)
The objective of this study is to diagnose the regulation of public services in Ceará. The thesis started with a historic presentation of the origin and evolution of regulatory agencies in the United States, It compared North American and European regulatory patterns represented by the French and the British experiences and discussed the concept of regulation in public services, detailed pretexts, objectives and fundamental aspects that should characterize regulatory agencies. By examining how regulatory agencies emerged in Brazil at the federal as well as at the state level in the context of state reform during the Fernando Henrique Cardoso administration, it described the principal characteristic of Brazilian federal regulatory agencies furthermore it exposed the scenario and the conditions of ARCE´s creation. From this point on, the thesis described the agency´s actions by analyzing its institutional profile, standardization methods, supervision, conflict intermediation and process analysis. It also tackled the role of the agency in formulating public policies and its patterns of negotiations of services rates with civil society through its institutional social control mechanisms. Throughout the thesis, ARCE´s regulation difficulties were discussed having as a reference international standards while in the conclusion were presented numerous suggestions and propositions to improve regulation of public services in the state of Ceará.